Adaptive guidance and control of uncertain lunar landers in terminal landing phases. (August 2020) - Sun, Liang; Sun, Guang; Jiang, Jingjing
Highlights: Singularity-free requirements in desired attitude extraction are satisfied to avoid the constraint of pitch angle attitude. Unknown external disturbances and parametric uncertainties in lunar lander dynamics are handled by robust adaptive control. Ultimately uniformly bounded stability and tuning rules of designing parameters are derived. Abstract: A novel double-loop guidance and control strategy for under-actuated lunar landers in terminal landing phases is developed by using adaptive nonlinear control approach in this study. To derive the main thrust input and inner-loop desired attitude trajectory, the outer-loop position tracking guidance law is firstly developed based on the hyperbolic tangent functions to guarantee the constrained thrust and singularity avoidance of the desired attitudes. Then, to avoid the complicated analytic-derivative computing of the desired attitude trajectory, a stable second-order filter is employed to generate the command attitude trajectory for the inner-loop attitude motion. Finally, an adaptive attitude tracking controller is designed by combining the barrier Lyapunove function and the backstepping technique to get rid of the singularities of the Euler angles-based attitude kinematic Jacobian matrix. In addition, tuning rules for designing parameters in guidance law and attitude controller are derived based on the Lyapunov analysis, and the pose tracking errors in the closed-loop system ultimately converge to the small neighborhoods of the origin. An example is simulated to verify the effectiveness of the proposed control design approach.